Pengembangan Desain Produk Kemasan Kue di Dapur Kue Mimih dengan Menggunakan Metode Quality Function Deployment (QFD) - Turmuji, Ahmad; Poerwanto, Eko; Astuti, Marni (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2024)
The increasing competition in the business sector requires MSMEs to continuously innovate, including in product packaging design. UMKM Dapur Kue Mimih, a small business specializing in traditional cake production in Tangerang Regency, still uses transparent mica plastic packaging, which lacks visual appeal and does not reflect product quality. This study aims to identify key packaging design attributes valued by consumers and establish development priorities using the Quality Function Deployment (QFD) method and House of Quality (HOQ) analysis. This research employs a descriptive quantitative approach, involving 100 respondents as the consumer sample. The HOQ analysis results indicate that the most desired packaging attributes among consumers are practicality and portability (92 points), high-quality materials (84 points), and reusable multifunctional packaging (78 points). On the business side, the top technical priorities are product appearance (134.4 points), ergonomic design (101.7 points), and premium material selection (75.9 points). The findings reveal that implementing the QFD method in packaging design development can enhance product competitiveness and customer satisfaction. The recommendations from this study can be adopted by other MSMEs seeking to improve their packaging strategies more effectively.